Pemenuhan Hak Pilih Penyandang Disabilitas Perspektif Fiqh Siyasah pada Pemilihan Presiden 2024 di Kabupaten Pekalongan - Nur Fatimah Thobib; Yunas Derta Luluardi (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2025)
People with disabilities have equal rights to participate in the democratic process. In Indonesia, this right has been regulated in the constitution and various regulations, such as Law Number 8 of 2016 concerning Persons with Disabilities and Law Number 7 of 2017 concerning Elections. However, the reality on the ground shows that there are various challenges that hinder their participation in elections, including the 2024 Presidential Election in Pekalongan Regency. This study aims to examine the fulfillment of transgender political rights from the perspective of fiqh siyāsah and identify factors that influence their level of participation in the democratic process. This study uses an empirical juridical approach with a conceptual method, which analyzes how existing regulations are implemented. Primary data were obtained through interviews with the General Election Commission (KPU) of Pekalongan Regency and transgenders who participated as voters in the 2024 Election. In addition, secondary data were obtained from scientific literature, journals, and relevant regulations in various countries. The results of the study indicate that: The Pekalongan Regency KPU has made efforts to fulfill the political rights of transgender people in accordance with the provisions of Law Number 8 of 2016 concerning Persons with Disabilities, but its implementation has not been fully felt by the disabled group. In the context of fiqh siyāsah, there is a violation of Islamic principles that guarantee human rights and equality before the law.